Redes de conversas e afetos como potencialidades para as práticas curriculares e para a formação de professores da educação infantil - Rodrigues, Larissa Ferreira (2011)
It approaches the study of curricular and development processes in Early Childhood Education, in a way to problematize, value and live the languages’ composition, knowledge and affection, through exchanging teacher experiences and group actions, produced in chat networks that emerge in a City Center of Early Childhood Education of Vitória/ES. It engages to understand the way experiences, lived and told by teachers, can potentiate the configuration of new existential areas for curricular processes and continue formation, from a “cartography” of the affects that attended chat networks. It also “weaves” a theoretical debate, which consists in thought lines, mainly from Carvalho (2008, 2009a, 2009b, 2009c); Deleuze (1992,1994, 1997); Deleuze and Guattari (1992, 1994, 1995,1996,1998); Foucault (1979, 2006a, 2006b); Rolnik (2007), despite other authors. The theoretical and methodological options establish a field research between the procedure of the studies with the daily and the cartographic research. It uses, as an instrument of data production for participant observation, the record in field diary, the photographic record, the teachers’ narratives and talks and the formation experiences. Directions of the researches emphasis some teachers’ social desires about education and, among those, the ones which run though the configuration of new existential maps for curricular creation in DevirCriança; through development of politicization points, able to promote a new way of theoretical and practical connections; through the creation of new power relationships established by productive effects of power in curricular and formative practices; through micro-experiences’ appreciation in DevirConversasDocentes; and through the production of CurrículosCrianças. Finally, it proposes the appreciation of experiences, narrated and lived by teachers, like micro political actions, able to potentiate the continue formation, the production of a school curriculum in Early Childhood Education, and also realizes, in chat networks, potentials to “weave” a quality education, in order to conceive the school as an affective community.